BAHASANTARA : KETIKA KESALAHAN BERBAHASA DILIHAT SEBAGAI SEBUAH KEUNIKAN - Sya’baningrum Prihhartini (Fakultas Komunikasi, Sastra, dan Bahasa, 2013)
This paper discusses the uniqueness of the language learner or inter-language. Interlanguage, or bahasantara, shown from the mistakes of lan-guage produced by learners. Mistakes are part of the development process while demonstrating proficiency learners who have achieved the level of profi-ciency. By showing that the error is a unique language, this paper aims to change the perception that the error was a thorn in language acquisition, and is expected timbuk new understanding that the error is an indication of the de-velopment of language second language learners